Oxygen and sulphur dioxide additions to Sauvignon blanc : effect on must and wine composition - Coetzee, Carien (Stellenbosch : University of Stellenbosch, 2011)
Thesis (MScAgric (Viticulture and Oenology))--University of Stellenbosch, 2011.